2017
DOI: 10.1104/pp.17.01297
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar Trafficking Protein VPS38 Is Dispensable for Autophagy

Abstract: Phosphatidylinositol 3-P (PI3P) is a signaling molecule that controls a variety of processes in endosomal, autophagic, and vacuolar/lysosomal trafficking in yeasts and mammals. Vacuolar protein sorting 34 (Vps34) is a conserved PI3K present in multiple complexes with specific functions and regulation. In yeast, the PI3K complex II consists of Vps34p, Vps15p, Vps30p/ Atg6p, and Vps38p, and is essential for vacuolar protein sorting. Here, we describe the Arabidopsis (Arabidopsis thaliana) homolog of yeast Vps38p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 86 publications
(124 reference statements)
2
19
0
Order By: Relevance
“…Strikingly, homozygous Arabidopsis vps38 mutants are viable but display a range of defects consistent with aberrant endosomal sorting, vacuolar trafficking, and autophagy (this report; Lee et al, 2018 ), which are consistent with studies with yeast and mammalian cells that demonstrated the importance of PtdIn-3P to these processes ( Kihara et al, 2001 ; Itakura et al, 2008 ). In our study, the defects were confirmed by a pair of vps38 alleles, along with their rescue by a VPS38-FLAG transgene.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Strikingly, homozygous Arabidopsis vps38 mutants are viable but display a range of defects consistent with aberrant endosomal sorting, vacuolar trafficking, and autophagy (this report; Lee et al, 2018 ), which are consistent with studies with yeast and mammalian cells that demonstrated the importance of PtdIn-3P to these processes ( Kihara et al, 2001 ; Itakura et al, 2008 ). In our study, the defects were confirmed by a pair of vps38 alleles, along with their rescue by a VPS38-FLAG transgene.…”
Section: Discussionsupporting
confidence: 87%
“…To study the function(s) of Arabidopsis VPS38 genetically, we searched the available germplasm collections for T-DNA mutants impacting the locus. Two mutant lines were available from the Arabidopsis Biological Resource Center (ABRC) which were confirmed by DNA sequence analysis; one contains a T-DNA insertion within the 2nd exon after nucleotide 507 downstream of the start codon (SAIL_552_F02), which was designated here as vps38-1 , and a second contains a T-DNA insertion within the 5th exon after nucleotide 1,886 downstream of the translation start site (SALK_094540C), which was designated as vps38-3 based on the allele nomenclature of Lee et al (2018) ( Figure 3A ). Homozygous individuals were identified in the selfed F2 generation by PCR genotyping, indicating that plants missing VPS38, unlike mutants impacting other subunits of the class-III PtdIn-3 kinase complex ( Fujiki et al, 2007 ; Qin et al, 2007 ; Harrison-Lowe and Olsen, 2008 ; Lee et al, 2008b ; Xu et al, 2011 ; Wang et al, 2012 ), produce viable pollen that will germinate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations